1989
DOI: 10.1210/endo-124-2-1017
|View full text |Cite
|
Sign up to set email alerts
|

Direct Inhibitory Effects of a Somatostatin Analog, SMS 201-995, on AR4-2J Cell Proliferation via Pertussis Toxin-Sensitive Guanosine Triphosphate-Binding Protein-Independent Mechanism*

Abstract: Somatostatin has been demonstrated to negatively regulate pancreatic growth in vivo. In this study we used the AR4-2J rat pancreatic acinar tumor cell line to investigate the effect of a stable somatostatin analog, SMS 201-995 (SMS) on cell proliferation. SMS induced an antiproliferative effect on both serum or epidermal growth factor (EGF)-induced cell proliferation; exposure of the cells for 48 h to SMS caused a slight inhibition of serum-induced proliferation (maximal inhibition, 26%) and abolished the grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
43
0
2

Year Published

1992
1992
2007
2007

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(52 citation statements)
references
References 0 publications
7
43
0
2
Order By: Relevance
“…By way of a positive control, we have shown that RC-160 can inhibit the EGF-induced growth of the AR42J rat acinar cell line. This is consistent with the report by Viguerie et al (1989) who have demonstrated that the somatostatin analogue SMS 201-995 has direct inhibitory effects on AR42J cell proliferation via a mechanism independent of a pertussis toxin sensitive GTPbinding protein.…”
Section: Cellsupporting
confidence: 93%
See 1 more Smart Citation
“…By way of a positive control, we have shown that RC-160 can inhibit the EGF-induced growth of the AR42J rat acinar cell line. This is consistent with the report by Viguerie et al (1989) who have demonstrated that the somatostatin analogue SMS 201-995 has direct inhibitory effects on AR42J cell proliferation via a mechanism independent of a pertussis toxin sensitive GTPbinding protein.…”
Section: Cellsupporting
confidence: 93%
“…The data revealed that AR42J possesses somatostatin receptors which consist of a single class of high affinity binding sites with a Kd (0.20 nM) in the range of that observed by other groups (Viguerie et al, 1989).…”
Section: Cellmentioning
confidence: 62%
“…Somatostatin acts as a growth inhibitory factor in a variety of normal and tumor cells (2,9,10). We and others have demonstrated that somatostatin and analogues induce the stimulation of a membrane PTPase, which may be involved in the inhibitory effect of these peptides on cell proliferation (9,11,12,38).…”
Section: Discussionmentioning
confidence: 98%
“…Further, the rapid activation of SHP-1 following somatostatin addition in CHO cells coexpressing sst2 and SHP-1 raises the possibility that activation of SHP-1 is the initiating step for sst2 signal transduction leading to inhibition of cell proliferation. These hypothesis are strengthened by the observation that rat pancreatic tumor AR42J cells are sensitive to the antiproliferative effect of somatostatin analogs and highly express sst2 receptors and SHP-1 (10,16,35). Examining SHP-1 expression in cells sensitive to somatostatin analogs would add significantly to these conclusions.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation